An Implementation Of Information Technology Towards Improving Human Resource Management Control On The Quality Of Financial Reports Of Radio Republic Indonesia Medan - Mbera Mehuli; Ferry Fachrizal (Jurnal Scientia, 2024)
This study aims to analysed the impact of information technology implementation on enhancing human resource management control and its influence on the quality of financial reports at Radio Republik Indonesia (RRI) Medan. The application of information technology is expected to improve efficiency and accuracy in data management, including financial and human resource data. The research adopts a quantitative approach by collecting data through surveys and interviews with staff and management at RRI Medan. The results indicate that effective use of information technology contributes positively to management control, leading to improvements in the quality of financial reporting. Therefore, the implementation of information technology can serve as a solution to enhance transparency and accuracy in financial reporting within the public sector.